Neolanguage and “neutral language”: inclusive potentialities and/or conservative reactions (Research, Society and Development, 2022)
Resuming the understanding of "Neolanguage", from the movements, actions, contributions and struggles of different activists of the non-binary cause in Brazil, this sociological study seeks to broaden the discussions about the place where the debate of the so-called "gender inclusive language" , “neutral language” or “non-binary language” is inserted in different instances of the political debate and Brazilian social context, especially when crossed by the issue of plurality in the school environment - seen as a potential space for inclusion and/or (re)production of violence against non-normative bodies –, respect for gender identification/expression, reaction and appropriation of agendas by conservative-religious movements and the construction of public policies. From the electronic documentary research that generated the mapping of 26 (twenty six) Bills, between 2020 and 2021, linked to a conservative national anti-gender agenda of “prohibition of neutral language”, parallels are drawn between such discursive constructions. and the arguments used around a supposed “Gender Ideology”. As a result, it was possible to perceive how different groups signify Neolanguage as a gender technology and political agenda, to the extent that political representatives from different legislative spaces established their actions, as bills, inserted in the reconfigurations of the discursive scenarios of international reactionary agendas, in addition to enable reflection on the reasons for assuming the school space as a target space for such agendas.